Government ownership, informed trading, and private information - Ginka Borisova; Pradeep K. Yadav (University of Cologne, Centre for Financial Research (CFR), 2015)
We investigate the nature and extent of information asymmetry among traders in companies with government ownership. Consistent with a less transparent information environment, we find relatively less informed trading in the shares of firms with government presence, and specifically, fewer informed trades related to the skilled analysis of public information. At the same time, we also find that firms with government presence have a significantly higher proportion of informed trading that arises from explicitly private information, consistent with the literature on the self-serving influence of government stakeholders not necessarily committed to maximizing firm value.
Keywords: G32; D82; L33; 330; Government ownership; Privatization; Information asymmetry; Informed trading; Private information